Deficiency of N-myristoylation reveals calcineurin activity as regulator of IFN-γ-producing γ[delta] T cells - Rampoldi, Francesca; Porubský, Štefan; Popovic, Zoran V. (Journal of leukocyte biology, 2017)
Calcineurin-Nfatc pathway promotes development and function of IFNγ-producing γδ T cells.